Geriatric medicine bridges: Scotland – Costa Rica - F Morales-Martínez (The Journal of the Royal College of Physicians of Edinburgh, 2017)
This paper reviews the specialised geriatrics healthcare services of Costa Rica, with particular emphasis on the achievements made in the field of geriatrics following the author’s specialist tertiary education and training period at the Professorial Unit at the City Hospital, Edinburgh, 33 years earlier. The paper charts the development and consolidation of an educational programme of geriatrics in Costa Rica against a background of the changing demographic in this Central American nation and the consequent and compelling need for universal coverage of healthcare services targeted to meet the needs of the burgeoning population of older adults.